One new genus and one new species of freshwater crabs (Decapoda, Brachyura, Potamidae) from the Southern part of Vietnam - Thanh, Dang Ngoc; Hai, Ho Thanh (Academia Journal of Biology, 2014)
Dalatomon gen. nov. Dang et Ho Diagnosis: crab is small in size, the length (l) under 30 mm, carapace trapezoid form, flat, upper surface smooth. Ischium maxilliped rectangular, merus almost rectangular, exopod long, reaching to 1/3 merus external margin. Male terminal segment of abdomen equilateral triangular, low with round top, lateral border straight, moderately longer than VI segment. GO1 terminal segment in male with dorsal, broad semicircular fold, extending to 2/3 length of this segment. Etymology: this genus name is derived from its type locality at Dalat (Lamdong province, west highland of Vietnam), in combination with the genus name Potamon. The gender is neuter. Type species: Dalatomon soni sp. nov. Dalatomon soni sp. nov. Dang et Ho Holotype: 1 male; Allotype, 1 female, collected from the stream at Dalat city (Lamdong province), Vietnam. Coll. 3 July, 2005; Paratype: 2 males, collected from Dalat city (Lamdong province). Coll 3 July, 2005, deposited in the Zoological Museum, Institute of Ecology and Biological resources, Hanoi-Vietnam. Diagnosis: crab is small in size, carapace largely transverse trapezoid, flat, upper surface smooth. Epibranchial tooth small. Anterolateral tooth not developed. Frontal margin moderately concave, Antero-lateral angle rounded, lateral margin oblique. Postfrontal, postorbital cristae cleared, undulated down, reaching to the basis of the epibranchian tooth. Postfrontal and postorbital bilobed swollen. Semilunar, H-shaped grooves distinct. Ischium maxilliped rectangular with groove in middle, exopod straigth, reaching to 1/3 merus external margin. Merus rectangular, flagella long reaching over merus upper margin. Male terminal segment of abdomen equilateral triangular, low with round top, lateral border straight, longer than VI segment. Subterminal segment of GO1 in male with basal part narrowly elongated. Terminal segment with dorsal, broad semicircular fold, located in the first half part, extending to 2/3 of this segment. Distal part of terminal segment cylinder-shaped, curved down tip truncate with upper distal angle produced as sharp, small, transparent projection. G2 long, slender, distal segment shorter than basal segment. Ambulatory legs slender, long. Remarks: Dalatomon soni sp. nov. is firstly found in Dalat city (Lamdong province), southern Vietnam. This species distributed in streams of highland mountainous areas but with small quantities. This new species is closely related to others species belonging to genera Laevimon, Donopotamon, Thaipotamon, Pudaengon, Rathbulamon, Phaibulamon, Pilosamon that are found in the Catba island (northern Vietnam) and in the basin of the Mekong river of southern Vietnam, Laos and Thailand. These species has the same characteristics such as terminal segment in GO1 of male with dorsal, broad semicircular fold but this new species differs from others by small size of carapace, the location of semicircular fold, the form of distal part of terminal segment and several different features as well. Table 1 Comparison of principal characteristics of Dalatomon gen. nov. with Donopotamon Dang et Ho 2005 and Laevimon Yeo et Ng., 2005 Characteristics of male Dalatomon Donopotamon Laevimon Size of carapace Small, the length less than 30 mm Big, the length more than 40 mm, even to 70 mm. Big, the length more than 40 mm. Carapace form Largely transverse trapezoid, flat, upper surface smooth. Largely transverse trapezoid, flat, upper surface smooth Anterolateral region rugose and granulose. Carapace distinctly transverse, high; dorsal surface strong convex longitudinally and transversely; smooth. Postorbital cristae Not sharp moderately oblique. Slightly sharp, horizontally straight. Uncleared. GO1 Subterminal segment with basal elongated. Terminal segment long 1/2 times length of subterminal segment, distal part curved down. Terminal segent with dorsal, broad semicircular fold, located in the first half part, extending to 2/3 of this segment. Terminal segment cylinder-shaped, tip truncate with upper distal angle produced as sharp, small, transparent projection. Subterminal segment with basal large, distal part narrow, neck-like. Terminal segment with dorsal, broad semicircular fold, occupying almost completely half distal part of this segment, establishing dove-head in shape. Subterminal segment with basal slender. Terminal segment short, about 1/3 times of subterminal segment. Terminal segment subcylindrical; tip truncate with inner distal angle produced as sharp, narrow projection. Hump-like, in proximal part, distinctly shorter than half length of terminal segment. Third maxilliped Ischium and merus rectangualar; exopod straight, reaching to 1/3 merus external margin. Flagellum long, reaching over merus upper margin; but shorter than merus width. Ischium rectangular; merus squarish; exopod straight, reaching to 1/3 merus external margin. Flagellum long, reaching over merus upper margin. Ischium broadly rectangular; merus squarish; upper angles rounded. Flagellum long, subequal to merus width. VII segment of the abdomen Equilateral triangular, low with round top, lateral border straight. Triangular; lateral border concave. Narrowly triangular; lateral border cocave at middle.